A Review of Antenna Array Technologies for Point-to-Point and Point-to-Multipoint Wireless Communications at Millimeter-Wave Frequencies - G. Federico; D. Caratelli; G. Theis; A. B. Smolders (International Journal of Antennas and Propagation)
With the introduction of 5G communication systems operating in the mm-wave frequency range, new opportunities in terms of multimedia services and applications will become available. For this to happen, several technical challenges from an antenna standpoint need to be addressed. The achievements of high-gain characteristics and agile beamforming with wide-scan capabilities are the main targets of the ongoing research on mm-wave antenna arrays. In this paper, an up-to-date overview of antenna array technology for wireless communications at mm-wave frequencies is given. Particular focus is put on the review of the state-of-the art and most advanced antenna array concepts for point-to-point and point-to-multipoint radio links at said frequencies. Various figures of merit are assessed for a comprehensive analysis and bench marking of the technical solutions investigated in the presented survey.